Phillips curves, behavioral economics and post-Keynesian macroeconomics - Peter Skott (University of Massachusetts, Department of Economics, 2023)
Post-Keynesians have questioned the relevance of behavioral economics on methodological grounds, citing the predominant focus of the behavioral literature on possible deviations of individual behavior from extreme standards of perfect optimization. The very limited influence of behavioral economics on post-Keynesian economics is unfortunate, however: it would a serious mistake to ignore the insights and empirical evidence from behavioral economics. The influence of norms of fairness on wage formation and inflation is used to illustrate this argument.
Keywords: E12; E31; E71; 330; distributional conflict; inflation; wage norms; wage stickiness; path dependence; methodology